GENE MAPPING: BASICS, TECHNIQUES AND SIGNIFICANCE - NIMBALKAR, VIKRAM; CHIKTE, DEEPALI; RAMAN, TEJAL; MANIYAR, SAHIL; GAIKWAD, PANDURANG (International Journal of Clinical and Biomedical Research, 2015)
Watson says, "Like the system of interstate highways spanning our country, the map of the human genome will be completed stretch by stretch". It may be possible to use genetic information to diagnose the disease accurately and to predict a patient’s likely response to a particular medicine or treatment. For whole genome mapping development and application of mapping, sequencing and computational tools are very essential and also linkage, physical and sequence maps are required to put the information together. For most genome mapping projects involve markers consisting of a unique site in the genome and should be independent of any particular experimental resource. For mapping purpose the DNA and RNA identification is essential. These genes are identified by hybridizing DNA clones against Northern blot, cDNA libraries, Zoo blot, Western blot and Southern blot of genomic DNA digested with rare cutter restriction endonuclease. The various experimental studies of gene mapping have extended our understanding of the genetics. This has allowed the investigators to detect a particular gene, which is responsible for the disease. Recent studies have shown the various effective and scientific gene mapping techniques and gene identification methods, which are helpful to diagnose a particular disease. It is easy for the doctor to give right medicine to the right patient to cure the disease when he can identify the defective gene responsible for disease. This article reviews the details of identification techniques of genes, gene mapping with broad applications. KEY WORDS: Gene mapping; Restriction mapping; Fluorescent in situ hybridization (FISH); Sequenced tagged site (STS) mapping; Somatic cell hybridization.